Effectiveness of Goji Berries (Lycium barbarum) Extract and Some Nanoparticles Loaded on Gelatin Film on Microbial Content of Labneh - Oroba Bahjat Shihab; Mohammed Ahmed Jassim; Hashim Mohammed Zehraw (Iraqi Journal of Industrial Research)
This study was conducted to evaluate the effect of Lycium barbarum extract, Chitosan nanoparticles (ChNPs) and Nanotitanium dioxide (TiO2 NPs) loaded on Gelatin films on the microbial content of labneh during different storage periods. The samples were divided into seven treatments which included (T1) non-coated labneh, (T2) labneh coated with gelatin membranes, (T3) labneh coated with gelatin membranes and Lycium barbarum extract, (T4) labneh coated with gelatin films and ChNPs, (T5) labneh coated with gelatin films treated TiO2NPs, (T6) Labneh coated with gelatin films, Lycium barbarum and ChNPs, (T7) Labneh coated with gelatin films, Lycium barbarum and TiO2 NPs. The total number of bacteria decreased after loading with the membranes for each specific period of time, and the treatment with T7 was the best, as the total number of bacteria decreased to 9.93 log/gm compared to the two controls (T1, T2), which amounted to (15.58, 13.47 log/gm) after 14 days of storage, respectively. While the numbers of Lipolytic and Proteolytic bacteria, yeasts and molds did not show any growth at the time of one day, with the prolonged storage period, the gradual increase in the total count of bacteria occurred for all treatments, it reached the highest numbers at the time of 14 days. Treatment T7 was the best in reducing the numbers of both lipolytic and proteinolytic bacteria, as well as yeasts and molds.